Escrito na areia: notas para um arquivo da participação - Marta Branco Guerreiro (Midas: Museus e Estudos Interdisciplinares)
This essay is about three participatory projects of the Fundação Calouste Gulbenkian: “Entre Vizinhos”, “O Poder da Palavra”, and “15/25 Imagina”. I have been following them since 2021 as a researcher, and I felt the need to create an archive that would allow me to analyse the processes of this participation. Although the final result of the participatory process (e.g., exhibitions, programming, public sessions) is the visible side of these long paths, often the middle steps that shape them end up being only in internal reports or in the memory of the participants. I propose to analyse the methodologies used, giving them visibility, but also adopting them in my own research, creating continuity between participant observation and academic writing, between process and thought. Following the idea of “situated knowledges” of the philosopher Donna Haraway, the place I occupied as a participant, being both inside and outside the projects, will be reflected in my position as a researcher, assuming that the lived experience will have an echo and influence in my investigation, just as my presence may have had in the projects. The methodology used throughout the participatory process changes the relationship between the various actors involved (artists, mediators, and participants outside the museum). This continuous construction is essential to understand the path of participation as a process, hence the need to create a methodology for building an archive of the intangible, the unarchivable: movements, sensations, silences, antagonisms, futures. It is an archive for a new way of thinking.